Efeitos da terapia de reposição com doses fisiológicas de testosterona sobre a reatividade vascular coronariana em ratos espontaneamente hipertensos orquiectomizados - Diaz, Juan Carlos Arapa (2019)
It is believed that the decrease of testosterone (T) in men favors the development of cardiovascular diseases, attributing to T a possible protective role for the cardiovascular system. In view of this context, our study aimed to evaluate the effects of T-replacement therapy on coronary vascular reactivity. All procedures were approved under No. 062/2017 – CEUA/UFES. Adult hypertensive male rats SHR (Spontaneously Hypertensive Rat) at 10 weeks of age were used. The animals were orchiectomized at 8 weeks (ORX group) and immediately started treatment with testosterone (0.5 mg / kg, sc) for 15 days (ORX + T group) or aromatase inhibitor (0.1 mg/kg/day via gavage - ORX + T + AI group), the SHAM animals underwent the same surgical procedure, however, without the removal of the gonads. Systolic blood pressure (SBP) was measured by tail plethysmography. Weight parameters were collected. Coronary vascular reactivity was conducted according to the Langendorff method and bradykinin curves (10-10 to 10-6 M) before and after inhibitors of nitric oxide synthase (Nω-Nitro-L-arginine methyl-éster - L-NAME 100 μM) and cyclooxygenase (Indomethacin - INDO 2.8 μM) isolated or combined with CYP inhibitor (clotrimazole - CLOT 0.75 μM) or combined with potassium channel blocker (Tetrabutylammonium - TBA, 0.75 mM) were performed. The expression intensity of the eNOS, COX-1, COX 2, gp91phox and Akt proteins were quantified by the Western blotting method. The labeling protocol for the synthesis of NO, superoxide anion (O2 •-) and hydrogen peroxide (H2O2) in coronary arteries was by spectrofluorimetry. The relative weight of the prostate and seminal vesicle decreased, however, those of the adrenal and pituitary increased by orchiectomy and were partially or totally reversed by T. SBP was lower in ORX group, with not changes in ORX + T group. The baseline coronary perfusion pressure was not altered in all studied groups, and NO and PGI2 participated in the modulation of coronary pressure in SHAM, ORX and ORX + T groups. The BK relaxation was not altered in the ORX group, and increased in the ORX + T and ORX + T + AI groups, with no difference between the latter groups. The NO, PGI2 and EDH participated in relaxation to BK in the SHAM and ORX groups, and only NO and EDH (which was greater) in the ORX + T group. The expression of eNOS, COX-1, COX-2, and gp91phox was not altered by orchiectomy or T, but the expression of Akt increased in the ORX group and was not restored in the ORX + T group. The synthesis of NO was not altered in all studied groups, on the other hand, the levels of O2 •- and H2O2 increased in the ORX + T group. In conclusion, our main finding is that replacement therapy with a physiological dose of testosterone improves relaxation to BK independently of the aromatization in the coronary vascular bed from orchiectomized SHR, with an increase in EDH [epoxy-eicosatrienoic acids (EETs) stimulating potassium channels and the likely participation of H2O2]. The characterization of these mechanisms could lead to a better understanding of the effects of treatment with testosterone in the coronary vascular bed, in addition to contributing to the development of improved therapeutic strategies for the treatment of hypogonadism and cardiovascular diseases.